Coleoptera: Scarabaeidae Observations on the behavior of a tropical rain forest dung beetle, Megathoposoma candezei (Harold) - Wille, Alvaro (1973)
Megathoposoma candezei dung beetles at the southerft base of Cerro Nara, 17 km north of the mouth of the Savegre River, on the southern Pacific slope of Costa Rica, are diurnal, in contrast with the Mexican populations; there are from 15 to 19 beetles per 50,000 m2 at 760-780 m elevation; below 600 m populations diminish considerably. Among the more obvious protective mechanisms are cryptic coloration and thanatosis which may last over two hours. These beetles avidly seek human excrement which they make into almost perfect balls, coat with mud, and buey in superficial chambers where they spend about 60 hours consuming them.Copulation takes place over the food pile, which represents the most primitive leve1 of sexual behavior so far known in Scarabaeini; rolling of the dung balls by couples was not observed.